Privacy - Tobias Matzner; Carsten Ochs (Internet Policy Review, 2019)
This contribution provides a short introduction into the conceptual and socio-technical development of privacy. It identifies central issues that inform and structure current debates as well as transformations of privacy spurred by digital technology. In particular, it highlights central ambivalences of privacy between protection and de-politicization and the relation of individual and social perspectives. A second section connects these issues to the influential texts and discussions on digital privacy. In particular, we will demonstrate privacy in digital societies is to be conceived in a novel way, since contemporary socio-technical conditions unsettle central assumptions of established theories: forms of perceptions, social structure or individual rights. Thus, a final third paragraph summarises theoretical innovations triggered by this situation – especially research from computer science to the social sciences and law and philosophy highlighting the requirement to take groups, social relations and broader socio-cultural contexts into account.
Keywords: 300; Privacy; Contextual integrity; Autonomy; Liberalism; Sociotechnical context